Guru Profesional serta hubungannya dengan prestasi belajar siswa - Masrur Huda; Bahtiar Hariyadi (EDUCATIO : Journal of Education, 2017)
The problem in this research is the professionalism of teachers and low student learning outcomes. The purpose of this research is to know the extent of the significant relationship between the professionalism of teachers with the learning outcomes of Islamic religious education. The type of research used is the ex-post facto research correlation. The population of this study amounted to 42 students. Samples were taken based on Nonprobability technique. Data collection techniques using questionnaires and documentation. The data analysis used is the correlation of product moment. The results of the study were obtained that the value of the correlation coefficient R count 0.653 and the value R table 0.304 then R count > R table. The value of coefficient of determination is indicated by the R square number or which is the quadratic result of the correlation value, i.e. 0.6532 = 0.426. The professionalism contribution of teachers with the learning outcomes of Islamic education is 42.6% and the remaining 57.4% is influenced by variables or other factors. This means that there is a significant relationship between the professionalism of teachers and students